Study of Mechanical Properties of Polymer Concrete by Manufactured Sand and Orthophthalic Polyester Resins: Improving the Mechanical Properties of Polymer Concrete with Orthophthalic Polyester Resins (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Recently, a number of researches have involved improving the concrete technology requirements through advanced research. These studies involved high strength concrete HSC, were highly dependent on the quality of ingredient– materials. HSC production potentially involves several trial mixes and uses high quantities of fine materials thus making it very costly and time consuming. The objectives of this study were to reduce the production cost, time required and to improve HSC properties by providing control mixes and using Orthophthalic polyester resin. This was done by experimentally investigating the HSC production using 100 replacement of cement and water by Orthophthalic polyester resin and selecting the optimum replacement content. All concrete mixes were homogeneous in fresh concrete state, did not show any sign of segregation. Orthophthalic polyester resin additions further improved the workability. At the age 7 days, all concrete mixes achieved the cube compressive strength between 60 to 70MPa. Tensile and flexural strength were increased using Orthophthalic polyester resin using Orthophthalic polyester resin. Higher strength concrete showed low ductility because the ultimate strain was found less than 0.35, there was In General 10 Orthophthalic polyester resin content was found the optimum.